First ply failure analysis of composite plates / Jamaluddin Mahmud, Valliyapan D. Natarajan and Isfanizam Ismail - Mahmud, Jamaluddin; Natarajan, Valliyapan D.; Ismail, Isfanizam (2004)
This paper is aimed to simulate the failure of selected fiber reinforced composite plates under transverse loading. A mathematical model and computational model are presented for the aJ1alysis.Higher Order Shear Deformation plate theory is utilized to predict the deformation of the plat.es. A failure criterion with the existence of coupling terms to determine the mode of failure for compositeplat.es is employed to predict. the failure. The uniqueness of this criterion compared to all other existing criteria is that it. includes the coupling terms, which relate the interaction between the longitudinal stress and the transverse stresses. As a consequence, it allows the interaction between the fiber properties aJ1d the matrix properties in terms of the strength of the material, which other failure criteria have neglected. Variation of material properties through thickness is used and accommodated by a discrete layer approach. A program based on a finite element method is developed using Fotran-90 to determine the lamina stresses. These stresses are then used in the present. failure model to determine the First Ply Failure. Finally, the First Ply results for various composite plates are analyzed. The results obtained with current failure criterion are also compared with the results obtained with existing failure criteria. The stresses distribution obtained have proved that the present finite-element program could determine lamina and inter-lamina stresses accurately when compared to the exact solutions. The results of the failure analysis have shown that the present failure models could offer a better prediction of failure for any composite laminate.